2022
DOI: 10.3389/fimmu.2022.1009530
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor effects of polysaccharides from Tetrastigma hemsleyanum Diels et Gilg via regulation of intestinal flora and enhancing immunomodulatory effects in vivo

Abstract: Tetrastigma hemsleyanum Diels et Gilg is a traditional Chinese herbal medicine with high medicinal value, and antitumor, antioxidant and anti-inflammatory biological activities. However, while several studies have focused on flavonoids in Tetrastigma hemsleyanum tubers, there are few studies on the enhanced immune effect of Tetrastigma hemsleyanum polysaccharides (THP). In this study, we evaluated the antitumor effect of THP in a lung tumor model and explored the mechanism of antitumor activity through intesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…Cytokines are highly active multi-kinetic protein-peptide molecules produced via immune cells and other related cells, which mainly mediate and regulate the immune response and inflammatory reaction and are involved in tissue repair, among others ( Schoenaker et al, 2018 ). According to the previous articles, some plant-derived polysaccharides mitigate CTX-mediated immunosuppression through immune cell activation, thus promoting cytokine secretion ( Zhou et al, 2018 ; Yang et al, 2021 ; Zhou et al, 2022 ). In this study, MLP modulates immunosuppression of chicks through elevating these six cytokine levels, conforming to prior results.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines are highly active multi-kinetic protein-peptide molecules produced via immune cells and other related cells, which mainly mediate and regulate the immune response and inflammatory reaction and are involved in tissue repair, among others ( Schoenaker et al, 2018 ). According to the previous articles, some plant-derived polysaccharides mitigate CTX-mediated immunosuppression through immune cell activation, thus promoting cytokine secretion ( Zhou et al, 2018 ; Yang et al, 2021 ; Zhou et al, 2022 ). In this study, MLP modulates immunosuppression of chicks through elevating these six cytokine levels, conforming to prior results.…”
Section: Discussionmentioning
confidence: 99%
“…18 Polysaccharides can resist tumor development by activating macrophages and lymphocytes, promoting cytokine secretion, and improving host antitumor immune function. [19][20][21] Macrophages are the primary immunoregulatory cells in tumors and play a vital role in the tumor immune response. 22 The polarization of TAMs is ubiquitous in tumorigenesis and development.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Historical records indicate that the roots of T. hemsleyanum have been used to treat high fever, pneumonia, and venomous snake or insect bites in children [11,13]. Modern pharmacological studies have also demonstrated various beneficial effects of T. hemsleyanum, including anti-inflammatory, antibacterial, antiviral, hypoglycemic, immunomodulatory, and antineoplastic effects [12,[14][15][16][17]. T. hemsleyanum is often used as an ingredient in Chinese patent medicines for various conditions.…”
Section: Introductionmentioning
confidence: 99%